Japanese Language Teachers’ Perception and Implementation of Classroom Action Research (CAR) - Nuria Haristiani; Amelya Septiana; Dewi Kusrini (Universitas Negeri Semarang, 2023)
Classroom Action Research (CAR) facilitates teachers to improve the quality of learning and teaching and works with them to develop and understand engaging context-specific research. In this study, 193 Japanese language teachers’ perceptions of CAR were qualitatively explored through Classroom Action Research’s survey to know the Japanese language teachers’ perceptions and abilities of research, especially at the high school level. A questionnaire consisting of open-ended questions was utilized to collect the data. The results revealed that most teachers don’t have sufficient capacity and ability to do the research, but they considered that research is a crucial skill. Participants who have done CAR mostly use it for getting promoted, and only a few of them use it to develop the quality of teaching. The survey results also showed that many teachers never did CAR based on the structured way or never done it at all. This study reveals that the ability of the teachers to do the research needs to be improved extensively. Keywords : Jurnal Pendidikan Bahasa Jepang Japanese Education JournalClassroom Action ResearchJapanese Language Education